The Morphology of the Solar Wind Magnetic Field Draping on the Dayside of Mars and Its Variability. Issue 8 (24th April 2018) - Fang, Xiaohua; Ma, Yingjuan; Luhmann, Janet; Dong, Yaxue; Brain, David; Hurley, Dana; Dong, Chuanfei; Lee, Christina O.; Jakosky, Bruce
Abstract: The magnetic field draping pattern in the magnetosheath of Mars is of interest for what it tells us about both the solar wind interaction with the Mars obstacle and the use of the field measured there as a proxy for the upstream interplanetary magnetic field (IMF) clock angle. We apply a time‐dependent, global magnetohydrodynamic model toward quantifying the spatial and temporal variations of the magnetic field draping direction on the Martian dayside above 500‐km altitude. The magnetic field and plasma are self‐consistently solved over one Mars rotation period, with the dynamics of the field morphology considered as the result of the rotation of the crustal field orientation. Our results show how the magnetic field direction on the plane perpendicular to the solar wind flow direction gradually departs from the IMF as the solar wind penetrates toward the obstacle and into the tail region. This clock angle departure occurs mainly inside the magnetic pileup region and tailward of the terminator plane, exhibiting significant dawn‐dusk and north‐south asymmetries. Inside the dayside sheath region, the field direction has the greatest departure from the IMF‐perpendicular component direction downstream of the quasi‐parallel bow shock, which for the nominal Parker spiral is over the dawn quadrant. Thus, the best region to obtain an IMF clock angle proxy is within the dayside magnetosheath at sufficiently high altitudes, particularly over subsolar and dusk sectors. Our results illustrate that the crustal field has only a mild influence on the magnetic field draping direction within the magnetosheath region. Plain Language Summary: According to the classic magnetic field draping theory, when the solar wind plasma encounters unmagnetized planetary bodies, the entrained interplanetary magnetic field (IMF) would pile up and drape around as the flow is diverted. Under this approximation, the draped field lines maintain an orientation similar to the upstream IMF in the plane perpendicular to the solar wind flow direction. However, the real morphology of the magnetic field draping at Mars has been poorly understood. In this study, we apply a state‐of‐the‐art global model to investigate the degree of distortion of the draped field lines when the complex Mars‐solar wind interaction is self‐consistently accounted for. Our results illustrate that when the IMF penetrates the magnetosheath edge into lower altitudes, the magnetic field lines may be so distorted and bent that their directions significantly deviate from the expectation from the classic field draping scenario. Our study reinforces the need to change any remaining notion of Mars in field line draping as a nonmagnetic planet. Moreover, this work presents a practical approach for inferring the IMF direction when direct measurements of the pristine solar wind are not available. Key Points: The clock angle of the field within the dayside magnetosheath is a reasonable proxy for the IMF The magnetic field clock angle departure increases with decreasing altitude and increasing SZA The draping direction departure is the greatest downstream of the quasi‐parallel bow shock